Panel 2: Natural climate solutions - Rangwala, Imtiaz, author; Rittenhouse, Bruce, author; Schisler, George, author; Neely, Bets, author; O'Malley, Robin, author; Rondeau, Renée, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2018)
Panelists discuss the benefits for nature and people with natural climate solutions.
Natural climate solutions
Moderator: Renée Rondeau. Panelists: Imtiaz Rangwala, Bruce Rittenhouse, George Schisler, Betsy Neely, and Robin O'Malley.
Presented at the 2018 CNHP Partners Meeting held on March 9, 2018 in the Grand Ballroom D, Lory Student Center, Colorado State University Campus, Fort Collins, Colorado.
Keywords: Colorado; conservation; environment; climate